The Effect of Problem-Based Learning Model on Student Learning Outcomes in Acid-Base Material at MAN 3 Mandailing Natal - Rico Apryanto Rangkuti; Mariam Nasution; Nur Azizah Putri Hasibuan (LAVOISIER: Chemistry Education Journal, 2026)
Based on research, students are unable to distinguish between the concepts of acids and bases, and are unable to apply the existing formulas for acids and bases, resulting in students being less active, less able to explore their knowledge, and less able to express their ideas, thereby leading to low learning outcomes. This study aims to determine the significant effect of the Problem-Based Learning model on student learning outcomes in acid-base material. This study was conducted at MAN 3 Mandailing Natal from June 16 to June 26 in the even semester of the 2024/2025 academic year. The research method used in this study was a quasi-experiment, and the research sample consisted of 32 students in each of the experimental and control classes. In the experimental class, there were 16 male students and 16 female students, while in the control class, there were 12 male students and 20 female students. The data collection techniques used were learning outcomes and documentation. The main instrument used was a multiple-choice test consisting of 15 questions, which were then analyzed using a t-test. The results of the hypothesis test using SPSS version 24 software obtained significant data, namely 0.000 0.05, so H0 was rejected and H1 was accepted. This indicates that there is a significant effect of the Problem-Based Learning model on student learning outcomes in acid-base material at MAN 3 Mandailing Natal. The implication of this study is that the application of the problem-based learning model affects learning outcomes and motivates students to learn at MAN 3 Mandailing Natal.